Automatic understanding of acoustic speech signal pathology - WSZOŁEK, Wiesław (Archives of Acoustics, 2007)
In this work, parts of the research concerning a new concept of applying computer technique in pathological speech analysis have been presented. This new concept assumes that during the pathological speech analysis we are not aiming neither at the establishing of such or other signal parameters nor at the trying to classify them, but we tend to understand automatically the causes of deformation, which can be observed in the considered signal. Therefore the concept presented postulates the replacing the well known process of the pathological speech acoustic signal recognition by a more advanced method of analysis, which means a confrontation of the features, which are revealed in the signal during its transformation with features that could be expected basing on the knowledge gathered in the system concerning pathological factors deforming the true form of the signal. In the meaning of the term "automated understanding", this denotes a signal analysis of a deformed speech, which is oriented towards revealing the sources of the observed signal distortions, and not towards bare analysis of their patterns and diagnostic deduction based on their typology. In the work the basic elements of the proposed method are presented. Examples showing its essence were derived basing on the selected larynx pathology analysis.